Bimodal poly(ethylene-cb-propylene) comb block copolymers from serial reactors: Synthesis and applications as processability additives and blend compatibilizers. (8th November 2016) - Tsou, Andy H.; López-Barrón, Carlos R.; Jiang, Peijun; Crowther, Donna J.; Zeng, Yiming
Abstract: Two solution reactors in series are utilized to synthesize poly(ethylene-cb-propylene) comb block copolymers, P(E-cb-P), where the first reactor prepares vinyl terminated atactic polypropylene (aPP) macromers from propylene using an organometallic catalyst favoring beta methyl elimination and the second reactor copolymerizes aPP macromers with ethylene using a different organometallic catalyst capable of incorporating macromers. The products are P(E-cb-P) comb block polymers with bimodalities in molecular weight, composition, and long chain branching. Low molecular weight (MW) components are linear and of mixed compositions consisting of random copolymers of ethylene and propylene and residual vinyl terminated aPP macromers. High MW components are comb branched with constant composition, and block copolymers. Even though the PE backbone is immiscible with the aPP comb arms, the presence of linear low MW ethylene-propylene random copolymer prevents the high MW comb block components from self-association into segregated domains or micelles when it is blended into high density polyethylene (HDPE) or isotactic polypropylene (iPP). By hindering micelle formation, this bimodal P(E-cb-P) can be intimately entangled with HDPE and with iPP delivering extensional flow hardening when it was added at 5%. Extensional strain hardening is observed at 5% addition of the bimodal P(E-cb-P) comb block copolymer in 50/50 HDPE/iPP blends with exceptionally high strain hardening ratio. It was found that this bimodal P(E-cb-P) comb block copolymer can compatibilize immiscible blends of HDPE and iPP resulting in domain size reductions and diffused interfaces. The enhanced strain hardening observed in blends with the bimodal P(E-cb-P) comb block addition may arise from the increases in the blend interfacial area and the entanglement of the blocks within the homopolymer phases. Graphical abstract: Highlights: Poly(E-cb-P) comb block copolymers are synthesized via macromer incorporation. The Poly(E-cb-P) copolymers are effective rheology enhancer of HDPE and iPP. Poly(E-cb-P) copolymers compatibilize HDPE/iPP blends and provides strain hardening.